Corrigendum: Quadrigeminal plate arachnoid cyst presenting with eye movement related migraine: a rare case report - Graciela, Yemima; Shen, Robert; Tjahjadi, Mardjono (Medical Journal of Indonesia, 2023)
[This corrects the article DOI: 10.13181/mji.cr.236858]